EFFECT OF JOINT MOBILIZATION AND ENDURANCE TRAINING ON QUALITY OF LIFE IN PATIENTS WITH RHEUMATOID ARTHRITIS - Mathew, Sherin; Varadharajulu, G. (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted to compare the effect of pre and post intervention on Quality of life in Rheumatoid Arthritis patients. The study was conducted in Krishna hospital, Karad with a sample size 28 and the subjects were assessedon the basis of their chief complaints, history, thorough observation, palpation, examination, laboratory and radiographic investigations for confirmatory diagnosis.The patients who confirmed the diagnosis were given joint mobilization to all the peripheral joints, hot moist packs for upper and lower back and endurance training. The outcome measures used were Short Form-36 for Quality of Life, Visual Analogue Scale for pain and Six Minute Walk Test for endurance training. The eight components of SF-36 was calculated and totaled into mainly two components Physical Component Survey and Mental Component Survey. The mean of PCS pre treatment 36.19 and post treatment 46.42 and mean of MCS was 45.42 and 54.71.This shows that there was extremely significant difference in both PCS (P<0.0001) and MCS (P<0.0001) scores. The within group comparison showed statistically significant difference in pre treatment versus post treatmentwhich showed reduction in pain and increase in the endurance andimprovement in their Quality of Life.CONCLUSION-Based on the statistical results and interpretations it was concluded that joint mobilization and endurance training was effective in reducing pain, improve endurance and thereby improving Quality of Life in patients with Rheumatoid Arthritis. There was improvement seen in all components of SF-36 questionnaire, Visual Analogue Scale and Six Minute Walk Test.